Interview with Luis H. Francia on February 22, 2017 at Coffee Bean and Tea Leaf, Katipunan Avenue, Quezon City - Sollano, Francis C. (Archīum Ateneo, 2017)
Excerpt: Luis H. Francia is a multi-genre writer, editor, and teacher. His poetry collections include Her Beauty Likes Me Well (1979), The Arctic Archipelago and Other Poems (1991), Museum of Absences (2004), and Tattered Boat (2014). He has also written a memoir, Eye of the Fish (2001, winner of the 2002 PEN Open Book Award, and the 2002 Asian American Writers award); a history book, A History of the Philippines: From Indios Bravos to Filipinos (2010); collections of essays, Memories of Overdevelopment (1998) and RE: Reflections, Reviews, and Recollections (2015), winner of the National Book Award (given by the National Book Development Board and the Manila Critics’ Circle) for Best Collection of Essays in English in 2016. He has also written for the theater, Beauty of Ghosts (2010) and The Strange Case of Citizen de la Cruz (2012). Brown River, White Ocean (1993), an anthology that he edited, remains as one of the most important anthologies of Philippine Literature in English published in the United States. He was a regular contributor to The Village Voice and writes an online column for the Philippine Daily Inquirer.